Nrf2/HO-1–dependent inhibition of ferroptosis underlies the antioxidant effects of 5-O-methylvisammioside in colitis - Li, Donglin; Xu, Fagang; Wang, Wei; Jiang, Chuan; Cui, Wenwen; Guan, Zhong-an; Gu, Chao (Frontiers in Immunology, 2026)
BackgroundFerroptosis contributes to epithelial injury and chronic inflammation in ulcerative colitis, yet pharmacologic strategies that durably attenuate ferroptosis and restore barrier function remain limited. 5-O-Methylvisammioside (MeV) is a natural compound with putative antioxidant properties, but its anti-colitic mechanisms are unclear.PurposeTo determine whether MeV alleviates colitis by activating the Nrf2/HO-1 axis and constraining ferroptosis.MethodsAcute colitis was induced in male Sprague–Dawley rats using dextran sulfate sodium and animals were randomized to vehicle, DSS alone, two MeV doses, or mesalazine as a benchmark control. Clinical activity, colon length, and histopathology were quantified alongside epithelial barrier readouts (ZO-1, occludin), oxidative stress and ferroptosis markers (lipid reactive oxygen species, malondialdehyde/4-hydroxynonenal, iron accumulation, GPX4, ACSL4), and Nrf2/HO-1 activation, including nuclear translocation of Nrf2. In parallel, erastin-challenged Caco-2 cells were used to test whether MeV directly restrains ferroptosis; Nrf2 knockdown probed pathway dependency.ResultsMeV dose-dependently reduced disease activity and histological damage and partially normalized colon length. Barrier proteins were preserved, and lipid peroxidation and iron overload were diminished. MeV increased Nrf2 nuclear translocation and upregulated HO-1, restored GPX4, and lowered ACSL4, consistent with ferroptosis restraint. In vitro, MeV limited erastin-induced lipid ROS and cell injury; Nrf2 silencing blunted these protective effects, supporting pathway involvement. Mesalazine produced improvements of similar magnitude on selected endpoints.ConclusionMeV alleviates experimental colitis, at least in part by activating Nrf2/HO-1 to restrain ferroptosis and preserve epithelial barrier integrity. These findings nominate MeV as a ferroptosis-targeting candidate for colitis.